A Strategic Partnership: U.S.-Singapore Trade Cooperation in the Era of Prime Minister Lee Hsien Loong - HUE, TRUONG (University of Wah Journal of Social Sciences, 2024)
Singapore’s economy depends heavily on trade and exports, especially consumer electronics, information technology products, pharmaceuticals and financial services. The United States-Singapore Free Trade Agreement (FTA) took effect in January 2004, the United States’ first bilateral FTA with an Asian country and achieved significant trade results. The US-Singapore FTA has provided greater access for US companies, has been instrumental in enhancing bilateral trade, and provides US commitment to Singapore in other areas. The article is based on the perspective of hedging concrete realism to analyze and clarify trade cooperation between Singapore and the United States under Prime Minister Lee Hsien Loong, which is also the time when the two countries celebrate their 20th anniversary. year of FTA signing.